An empirical analysis of financial stress within South Africa and its apparent co-movement with financial stress emanating from advanced and emerging economies - Graham, Brydone (Rhodes University, Faculty of Commerce, Department of Economics, 2013)
The identification of financial stress, and an understanding of financial contagion on a global scale, is of critical importance to a South African economy that is becoming increasingly integrated into the global economy. The last decade has been characterised by periods of high economic growth, but also periods of significant financial instability culminating in global economic crises. This study examines the extent to which the South African financial system is exposed to distress abroad by identifying and measuring the co-movement of financial stress originating from within and outside South Africa. The study can be separated into two sections: the identification of financial stress and the measurement of financial contagion. Using monthly data for the period 2000 to 2012, three indices were constructed for the emerging markets, advanced economies and South Africa using varianceequal weighting. The indices were tested for contagion using the Johansen and Jesulius (1990) multivariate cointegration approach supplemented with basic OLS architecture and Impulse Response analysis. The results indicate the three constructed indices were highly accurate at identifying the intensity and timing of financial stress over the three regions respectively. It was found that the South African financial sector is highly susceptible to financial stress originating from advanced economies. The results obtained for financial stress emanating from emerging markets were not as conclusive and found to be insignificant. Overall, it is clear that the methods employed to identify financial stress are highly accurate and that South Africa is highly susceptible to financial stress originating from abroad. It is clear that advanced economies have a greater ability to affect financial stress in South Africa via contagion. It must be noted that this does not conclude that South Africa is not affected by emerging market crises, but that these crises tend to affect South Africa through advanced economy channels as defined within this thesis.
Keywords: Financial crises -- South Africa; Financial crises -- Developing countries; Globalization -- Economic aspects -- South Africa; International economic relations -- South Africa -- Economic conditions